Balancing Study and Work: An Analysis of Part-Time Employment among University Students and Its Implications for Human Capital Development - Nurmala, Evan Rosdiana; Narimo, Sabar (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study aims to explore in depth the experiences, challenges, and strategies of students in balancing their dual roles as learners and part-time workers. The phenomenon of working students is increasingly common; however, qualitative research examining their subjective perspectives remains limited. Using a qualitative case study approach, data were collected through semi-structured in-depth interviews with ten active students from various study programs who held part-time jobs in Solo. The findings indicate that balancing academic and work responsibilities is a dynamic process influenced by multiple factors. Effective time management, flexible work schedules, and social support from family, friends, and the campus environment are key to students’ success. Participants revealed that part-time work not only fulfills financial needs but also contributes to the development of independence, interpersonal skills, and relevant professional experience. Nevertheless, they also face significant challenges. The study concludes that the success of part-time student workers largely depends on a combination of adaptive personal strategies and strong external support